Can Entrepreneurship Education and Personality Encourage Students to Become Entrepreneurs? - Suryadi, Nanang; Anggraeni, Rila (Journal of The Community Development in Asia, 2023)
ABSTRACT Entrepreneurs are business people who remarkably contribute to the country's economic growth. The growing intention and interest in entrepreneurship will create new jobs, innovative products, and services. Entrepreneurial intent is essential in motivating students to pursue careers as entrepreneurs in their professional lives. This study aims to understand students' entrepreneurial intentions by analyzing the influence of entrepreneurship education and personality. Moreover, the conceptual framework built in this study used the theory of planned behavior (TPB) integrated with entrepreneurship education and individual personality. Data were collected using purposive sampling of students of the undergraduate entrepreneurship program. The structural equations were tested using WarpPLS software. The findings revealed that education regarding entrepreneurship and personality impacts subjective norms and attitudes. Furthermore, all the elements of the theory of planned behavior influence entrepreneurial intention. As a result, entrepreneurship education programs should cover management courses to improve business competency and develop positive emotions toward entrepreneurship.